An effective analytical system based on an ultraviolet atomizer for trace cadmium determination using atomic fluorescence spectrometry. Issue 39 (1st October 2018) - Yuan, Xin; Yang, Li; Liu, Siyan; Yang, Haiyan; Tang, Yuyi; Huang, Ke; Zhang, Mei
Abstract : A novel ultraviolet (UV) atomization atomic fluorescence spectrometry (UV-AFS) system was developed for the quantitative analysis of trace cadmium ions (Cd) without preconcentration. Abstract : A novel ultraviolet (UV) atomization atomic fluorescence spectrometry (UV-AFS) system was developed for the quantitative analysis of trace cadmium ions (Cd) without preconcentration. Cd 2+ can transform into Cd 0 and Cd hydride (CdH2 ) gas vapor after hydride generation (HG) with KBH4 . With the help of a simple, low power and low temperature UV atomizer, CdH2 can be converted to Cd 0 and thus the total Cd was detected. Due to the high atomization efficiency and low carrier gas dilution of the UV atomizer, the analytical system provides high sensitivity with a limit of detection (LOD) of 0.006 ng mL −1, which was comparable to those obtained by preconcentration methods. The relative standard deviation (RSD) ( n = 11) was better than 2.1% at a concentration of 0.5 ng mL −1 . Its application was demonstrated by analyzing Certified Reference Materials and food samples for ultra-trace detection of Cd 2+ .